Utopia is creepy : and other provocations - Carr, Nicholas G., 1959- (W.W. Norton & Company, 2016)
"A freewheeling, sharp-shooting indictment of our tech-besotted culture by the Pulitzer Prize finalist. Over the past dozen years, Nicholas Carr has made his name as an agenda-setting writer on our complicated relationship with technology. Gathering posts from his blog Rough Type as well as seminal pieces published in The Atlantic, the MIT Technology Review, and the Wall Street Journal, he now provides an alternative history of the digital age, chronicling its roller-coaster crazes and crashes (remember MySpace or Second Life?). Ground-breaking essays such as 'Is Google Making Us Stupid?' and 'Life, Liberty, and the Pursuit of Privacy' dissect the logic behind Silicon Valley's 'liberation mythology, ' laying bare how technology has both enriched and imprisoned us--sometimes at the same time. A forward-looking new essay rounds out the collection. With searching assessments of topics from the future of work and play to free choice and the fate of reading, Carr once again challenges us to see our world anew"--Provided by publisher.